Chemistry Taught With Augmented Reality And Learning Outcomes: A Review - Fitriana, Nurin; Rahayu, Sri; Agustina, Indah Nur (JURNAL PENDIDIKAN SAINS (JPS), 2024)
The point of this inquiry is to decide the effect of utilizing increased reality within the learning preparation and what materials frequently utilize AR at different levels of instruction and to decide the adequacy of AR in accomplishing learning results and expanding understanding of chemical concepts. The research strategy could be an orderly writing survey of different observational things about and related writing. Utilizing the SCOPUS database, mapping was carried out utilizing PRISMA charting innovation to get 40 articles recorded by Scopus. The inquiry about comes about appears that AR isn't as it was utilized to ponder chemistry subjects in essential and auxiliary instruction, but too to study progressed subjects such as response components and ghastly investigation in higher education. The most important reason for utilizing AR in chemistry learning is its capacity to supply three-dimensional visualization and interactivity to assist understudies in understanding complex and theoretical concepts. AR makes immersive and locks in learning encounters, increments understudy inspiration and engagement, and empowers secure and open virtual tests. The observational proof appears that the utilization of AR moves forward data maintenance, conceptual understanding, and down-to-earth aptitudes, essentially making strides in students' learning results and conceptual understanding. AR innovation has demonstrated success in accomplishing superior learning results and developing students' understanding of chemistry concepts, making it an imaginative and important instrument in chemistry instruction.